2008
DOI: 10.1063/1.2831665
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dielectric properties in single crystal-like BiFeO3 thin films grown by flux-mediated epitaxy

Abstract: We have fabricated single crystal-like BiFeO 3 ͑BFO͒ thin films by flux-mediated epitaxy using pulsed laser deposition ͑PLD͒. The Bi-Cu-O flux composition and its thickness were optimized using composition spread, thickness gradient, and temperature gradient libraries. The optimized BFO thin films grown with this technique showed larger grain size of ϳ2 m and higher dielectric constant in the range of 260-340 than those for standard PLD grown films. In addition, the leakage current density of the films was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…In other words, the coexistence of three types of conduction mechanisms is beneficial to strongly improve leakage properties. Second, the reduced leakage current indicates partial codoping Ho and Mn in the perovskite BiFeO3 thin films can control the oxygen vacancies, [29] and the decrease of leakage current density may indicate effective control of charge fluctuation by the doping of RE 3+ and Mn ions into BFO. The strong bond strength of RE-O controls the volatilization of the Bi and stabilizes the perovskite structure.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the coexistence of three types of conduction mechanisms is beneficial to strongly improve leakage properties. Second, the reduced leakage current indicates partial codoping Ho and Mn in the perovskite BiFeO3 thin films can control the oxygen vacancies, [29] and the decrease of leakage current density may indicate effective control of charge fluctuation by the doping of RE 3+ and Mn ions into BFO. The strong bond strength of RE-O controls the volatilization of the Bi and stabilizes the perovskite structure.…”
Section: Resultsmentioning
confidence: 99%
“…It is well‐known that the intrinsic effects, such as presence of oxygen vacancies caused by the volatilization of Bi 3+ , existence of Fe 2+ due to the electrical instability of Fe 3+ , formation of secondary phase and the extrinsic effects, such as porosity in the microstructure, grain boundary, etc., are considered as important factors for the large J value . Formation of oxygen vacancies induces impurity energy level in the band gap and increases the free carrier density by hopping of electrons to these defect levels . Therefore, partial doping of rare earth ( A‐ site) and/or transition metal ions ( B‐ site) in the perovskite BFO control the oxygen vacancies and stabilize the perovskite structure through charge compensation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, incorrect Bi concentration in the targets can create secondary phases, such as Fe 2 O 3 [6,7], while improper oxygen environments during laser ablation can lead to pockets of Bi 2 O 3 [6]; on the other hand, high growth temperatures can also lead to cation diffusion across the thin film interfaces [8]. Additionally, it has been found that oxygen vacancies could induce significant leakage current [9,10]. Among the secondary phases that can be created during the BFO deposition process, there has been a significant interest in Fe 2 O 3 phases found in BFO thin films.…”
Section: Introductionmentioning
confidence: 99%